EMPLOYMENT OF HIGHER EDUCATION INSTITUTION AND VOCATIONAL COLLEGE GRADUATES WITH DISABILITIES IN MOSCOW: COMPARATIVE ANALYSIS - Elena V. Arzhanyh; Olga A. Gurkina (Moscow Polytechnic University, 2016)
The article compares various aspects of employment of higher education institution and vocational education college graduates with disabilities in Moscow. A comparative analysis is based on the sociological research data. We observe the qualitative differences in the process of employment and in the position on the labor market of the two groups of young professionals. University graduates are more often guided by the motives and factors associated with non-material aspects of work. In contrast, college graduates are characterized by "materialism": focus on earnings accompanied by rejection of getting further education leads them to occupy positions with lower rates of payment. This stimulates the growth of discontent among this group of workers and increases intentions to change job. If the situation in supply for worker's specialties on the labour market will not change in a long term we can predict rising in popularity of higher education among school and vocational college graduates with disabilities of Moscow.